Pengaruh Kompensasi dan Fleksibilitas Kerja terhadap Kinerja Melalui Kepuasan Kerja sebagai Variabel Intervening pada Driver Shopeefood di Sidoarjo - Yusuf Al Alim; Budi Prabowo (LPPM Institut Nasional Laa Roiba Bogor, 2023)
Yusuf Al Alim1, Administrasi Bisnis, UPN “Veteran” Jawa Timur yusufalalim123@gmail.com1, ABSTRACT The goal of this study was to find out about the influence of compensation and work flexibility variables on performance through job satisfaction for Shopeefood drivers in Sidoarjo. This study uses a quantitative data approach. The data used are primary data obtained through questionnaires that have been answered by respondents. The formula used to determine the number of samples uses the Cochran sampling formula and the withdrawal technique uses purposive sampling with 100 Shopeefood driver respondents who run the latest orders in Sidoarjo. Path analysis is a research method used to find the significance of independent and dependent variables through intervening variables. From the research that has been done shows several levels of Shopeefood driver performance are not maximized and the data calculation produces a significance value which concludes that compensation has a significant effect on performance. Work flexibility has no significant effect on performance. Compensation has a significant effect on job satisfaction. Work flexibility has a significant effect on job satisfaction. Compensation has no significant effect on performance through job satisfaction. Work flexibility has no significant effect on performance through job satisfaction. Keywords: Compensation; Work Flexibility; Performance; Work Satisfaction